2022
DOI: 10.3390/agriculture12091445
|View full text |Cite
|
Sign up to set email alerts
|

Robot Path Planning Navigation for Dense Planting Red Jujube Orchards Based on the Joint Improved A* and DWA Algorithms under Laser SLAM

Abstract: High precision navigation along specific paths is required for plant protection operations in dwarf and densely planted jujube orchards in southern Xinjiang. This study proposes a robotic path planning and navigation method for dense planting of red jujube orchards based on the improved A* and dynamic window approach (DWA) algorithms using Laser Radar to build maps. First, kinematic and physical robot simulation models are established; a map of the densely planted jujube orchard is constructed using Laser Rada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 32 publications
0
6
0
1
Order By: Relevance
“…In 2020, Zhong 84 combined A∗ algorithm and adaptive window algorithm to simplify the calculation of risk cost function and distance cost, reduce the number of grid nodes, and realize smooth path tracking. In 2022, Li 85 used lidar to build a map and combined the improved A∗ algorithm with the DWA algorithm to realize the global path planning and real-time local path planning of plant protection operations in dwarf and dense jujube orchard. The U-shaped path exhibits an average error of 0.0269 m, whereas the linear path demonstrates a displacement error of 0.0247m.…”
Section: Research Progress Of Path Planning Algorithmsmentioning
confidence: 99%
“…In 2020, Zhong 84 combined A∗ algorithm and adaptive window algorithm to simplify the calculation of risk cost function and distance cost, reduce the number of grid nodes, and realize smooth path tracking. In 2022, Li 85 used lidar to build a map and combined the improved A∗ algorithm with the DWA algorithm to realize the global path planning and real-time local path planning of plant protection operations in dwarf and dense jujube orchard. The U-shaped path exhibits an average error of 0.0269 m, whereas the linear path demonstrates a displacement error of 0.0247m.…”
Section: Research Progress Of Path Planning Algorithmsmentioning
confidence: 99%
“…The method used the hybrid algorithm to achieve global and local path planning, and optimized path through evaluation function. Results showed that it was superior to traditional fusion algorithm [ 9 ]. Linz team proposed a method to conduct global and local robot path planning.…”
Section: Related Workmentioning
confidence: 99%
“…Other sensors, including LiDAR, cameras, and IMUs, can also be used by SLAM to produce a comprehensive map of the surroundings. The production of precise maps of fields and orchards is an important use of GNSS-based SLAM in PA [97]. GNSS-based SLAM may also be utilized for precise agricultural machinery guiding [98].…”
Section: Simultaneous Localization and Mappingmentioning
confidence: 99%